Ex vivo evaluation of the efficacy of depotphoresis method in root canal disinfection - Saeed Moradi; Siavash Moushekhian; Reza Karazhyan; Amir Ebrahimi (Dental Research Journal, 2023)
Background: Electrochemical disinfection of the root canal system (RCS) is introduced as an alternative to conventional irrigation. The aim of this study was to assess the efficacy of depotphoresis method in the disinfection of accessible and inaccessible RCSs. Materials and Methods: In this comparative in vitro study disinfection of Enterococcus faecalis-infected RCS using two methods, (1) depotphoresis and (2) sodium hypochlorite (NaOCl) irrigation plus passive ultrasonic agitation (PUA) took place on 40 extracted maxillary anterior teeth. Decoronation was done with a diamond disc, and the canals were instrumented. The roots were divided into two phases: the specimens with canal obstruction and the specimens without canal obstruction. The smear layer was removed, and the specimens were infected for 21 days with E. faecalis. After disinfection procedures, bacterial samples were taken using two sterile #35 paper points, and colony-forming units (CFU) were counted. Data were analyzed statistically using the Kruskal–Wallis test, with a significance level at P < 0.05, to indicate differences between depotphoresis and NaOCl plus PUA groups. Results: In both phases, Log CFU after depotphoresis treatment was significantly lower than NaOCl irrigation plus PUA treatment (P < 0.05). Conclusion: Treatment with depotphoresis was significantly more effective than NaOCl irrigation plus PUA treatment.